CUG-binding protein 1 regulates HSC activation and liver fibrogenesis - Xingxin Wu (Nature Portfolio, 2016)
Activation of hepatic stellate cells is a critical event in the development of fibrosis, which is driven by TGF-beta and inhibited by IFN-gamma. Here Wu et al. show that the RNA binding protein CUGBP1 is increased by TGF-beta signalling and promotes IFN-gamma mRNA degradation.